Self-harm among inmates of the Berlin prison system - Blees, Alexander; Jakobowitz, Sharon; Hofer, Jakob; Konrad, Norbert; Krebs, Julia; Opitz-Welke, Annette (Frontiers in Psychiatry, 2024)
Introduction: Self-harming behavior in prisoners is a prevalent phenomenon, with international studies estimating a 4% prevalence rate. However, studies on selfinjurious behavior in the German prison system are currently lacking. Therefore, our study aims to conduct an initial assessment. Methods: The Criminological Service for the Berlin Prison System distributed questionnaires on incidents of self-harm to all Berlin prisons, except for juvenile detention centers. The questionnaires were supplemented with medical data, such as psychiatric diagnoses and medication. Results: 62 questionnaires were returned, which could be attributed to 52 inmates. Compared to the average population in the Berlin prison system, the study sample exhibited variations in age, gender distribution and nationality. 94% of the inmates received a psychiatric diagnosis. Two-thirds of the male inmates had substance use disorders, while 83% of the female inmates had emotionally unstable personality resp. borderline disorders. Prior to self-harm, 87% of the inmates were administered psychiatric medication. Discussion: Our study found similarities between the study population and international studies in the distribution of certain characteristics. We assume that many of the postulated risk factors can also apply to Berlin prisoners. However, the study is limited by the small number of cases and the absence of a control group.In Berlin, there were around 2,500 prisoners and those in preventive detention (excluding pre-trial detention) on the cut-off date of 03/31/2022; in Germany as a whole, there were around 42,000 prisoners (1). According to a meta-analysis by Fazel et al., prisoners are more likely to suffer from mental disorders than the general population, which increases their risk of suicide and self-harm (2). The behavior of individuals not only affects those directly involved but also their immediate environment, including fellow inmates or staff (3). According to a 2014 study of nearly 26,000 Welsh and English prisoners, the prevalence rates of self-harm were between 5-6% in male and 20-24% in female prisoners, significantly higher than the prevalence in the general population of around